Combining Ability of Six Extra-Early Quality Protein Maize (QPM) Inbred Lines - Ofori, A.P. (University of Ghana, 2013)
Six extra-early QPM inbred lines from IITA were investigated using a partial diallel cross design. The objectives were to assess the hybrids and their parents for their agronomic performance. The six parents along with their hybrids (15) were evaluated using a Randomized Complete Block Design (RCBD) with three replications per site in four locations. Genetic correlations, general combining ability (GCA) and specific combining ability (SCA) effects as well as mid-parent heterosis were determined. Stability of grain yield and its relationship with other agronomic traits across four locations were also determined. Results of combined analysis of variance (ANOVA) revealed significant environmental effect for all the traits studied. Significant additive effect was observed for only grain yield whilst non-significant GCA and SCA effects were identified for all other traits. The GCA estimate identified parental lines P1, P3 and P5 as the high combiners for grain yield. The highest values for SCA and mid-parent heterosis for grain yield were observed in the crosses P1xP4, P5xP6, P1xP5 and P4xP6. The additive main effects and multiplicative interaction (AMMI) analysis revealed non-significant genotype by environment interaction (GEI) for grain yield whilst genotypic and environmental main effects were highly significant. However, the contribution of the environment was higher which suggests that anyone of the locations used in this study can be used for subsequent evaluations in order to manage the limited resources available for the testing programme.
Thesis (MPhil) - University of Ghana, 2013